Um grande oceano: Brasil e União Soviética atravessando a Guerra Fria (1947-1985) - Caterina, Gianfranco (2019)
This dissertation thoroughly analyzes the diplomatic relations between Brazil and the Soviet Union from 1947 to 1985. The main objectives are to closely assess the interactions between the two countries over a longer period than usual, and reassess the role of trade as the core of bilateral relations. It is argued that Soviet modernization had a lasting influence on the behavior of an important part of Brazilian political elites in their interactions with the USSR between the 1950s and 1980s. Even the emergence of an anticommunist military regime in Brazil in 1964 would not jeopardize relations between the two countries on a permanent basis. Similarly, the logic of bipolar antagonism, typical of the Cold War period, is not adequate to capture alone the increasingly complex nature of the relationship between Brazil and the USSR. It is analyzed how economic, political and strategic interests between the two countries converged in certain moments being guided, in important part, by the Soviet modernizing ideal. The conclusions are relevant because they aim to fill a gap in the history of Brazilian foreign policy in its interactions with the USSR, but also prove useful for scholars of Brazil's relations with the United States and China. In relation to the former, different Brazilian governments – in different contexts – tried to bargain better negotiation conditions with Washington, using their relationship with the USSR. Regarding the latter, this research has relevance for showing evidence about China's emerging competition with the USSR for influence in Third World countries – including Brazil – from the mid-1970s. Documents obtained in Brazil, Russia, the United States and Switzerland were used in the elaboration of this dissertation.